The Hemos mountains in the context of Byzantine cultural and economic influences on Early Medieval Bulgaria. - Marinow, Kirił (Balcanica Posnaniensia. Acta et studia, 2019)
The text discusses the importance of the Hemos mountain range (nowadays including Pre-Balkan, Stara Planina and Sredna Gora massifs) which separated the core territory of the early medieval Bulgaria in the North from the Byzantine lands in the South (almost through the entire so-called pagan or barbarian period of the Bulgarian state, i.e. from the end of 7th to the middle of 9th centuries), and divided the state in two geographically separated territories during the rest part of the existence of the so-called First Bulgarian Empire (from the second half of the 9th to the end of 10th and beginning of 11th centuries). The source investigation shows that especially during the first half of the period in consideration – the mentioned pagan (barbarian) period – the mountains really acted, to a certain degree, as a barrier for the Byzantine influences on the Bulgarians. That was because of the ideological (political) and religious differences between both the states.